INNOVATION IN PUBLIC SERVICES OF THE NATIONAL NARCOTICS AGENCY OF SURABAYA CITY IN THE DRUG PREVENTION PROGRAM - Aswir , Herwin; Pramono , Sapto; Roekminiati, Sri (International Journal of Multidisciplinary Reseach, 2025)
This study aims to analyze public service innovations implemented by the Surabaya National Narcotics Agency (BNN) in its drug prevention program. The complex public issue of drugs requires reforms in service delivery that are not only administrative but also participatory and collaborative. This study applies a qualitative approach through a case study design. Data were collected through in-depth interviews, observations, and documentation analysis of the drug prevention program implemented by the Surabaya BNN. The research findings indicate that innovations in public services are realized through active community participation as volunteers and cadres in the prevention, eradication, abuse, and illicit trafficking of narcotics (P4GN), the use of digital media for education, intersectoral collaboration, service target segmentation, and the application of data from drug-prone areas in program planning. These innovations demonstrate a shift in the BNN's function from program implementer to a liaison for community participation. Theoretically, these results are consistent with the new public service paradigm, new public governance, and the concept of public value. This study contributes to the development of public service innovation analysis and practical suggestions for strengthening drug prevention strategies that focus on public services.